Revitalizing Early Childhood Dance Learning: Supporting RA and TK Teachers - Nur Tanfidiyah; Subandji Subandji; Tri Utami (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to strengthen early childhood arts education through the revitalization of dance learning for Raudhatul Athfal (RA) and Kindergarten (TK) teachers in the Solo Raya region. The program addressed gaps in teachers’ pedagogical and technical competencies, limited instructional resources, and the lack of structured dance programs in early childhood education settings. A Community-Based Research (CBR) approach was implemented through sequential stages, including needs assessment, classroom observation, Focus Group Discussions (FGD), participatory training, and mentoring. Data were collected from 60 RA and TK teachers using interviews, questionnaires, observations, and group discussions. The results revealed that although schools acknowledged the importance of dance for children’s physical, emotional, and cultural development, teachers faced challenges in basic dance techniques, the use of learning media, and practical classroom implementation. The participatory training improved teachers’ understanding of children’s dance principles, fundamental movement skills, and strategies for integrating dance into thematic learning. In addition, teachers developed simple choreographies and learned to design age-appropriate performance activities. The mentoring phase further enhanced teacher confidence and increased the frequency of dance activities in partner schools. Overall, the program demonstrates that capacity-building initiatives in dance education contribute to improving the quality of arts education in PAUD institutions while also supporting cultural appreciation and holistic child development. Program sustainability is strengthened through collaboration with IGRA and IGTK Solo Raya.